Morus Rubra Extract Induces Cell Cycle Arrest and Apoptosis in Human Colon Cancer Cells Through Endoplasmic Reticulum Stress and Telomerase. (2nd January 2017) - Demir, Selim; Turan, Ibrahim; Aliyazicioglu, Yuksel; Kilinc, Kagan; Yaman, Serap Ozer; Ayazoglu Demir, Elif; Arslan, Ayse; Mentese, Ahmet; Deger, Orhan
ABSTRACT: Many studies have reported cytotoxic effects of different Morus species, but there have been only limited studies on the cytotoxic effect of Morus rubra . The aims of this study were to evaluate the cytotoxic effect of dimethyl sulfoxide extract of M. rubra and to investigate, for the first time, its probable cytotoxic activity in human colon cancer (WiDr) cells, together with the mechanism involved. The cytotoxic activity of extract was determined using MTT assay. The mechanism involved in the cytotoxic effect of extract was then evaluated in terms of apoptosis, and the cell cycle using flow cytometry, mitochondrial membrane potential (MMP) was investigated using the fluorometric method, and expression levels of telomerase and C/EBP homologous protein (CHOP) were investigated using reverse-transcription PCR (RT-PCR). M. rubra extract exhibited moderate selective cytotoxicity on colon cancer cells compared with fibroblast cells. Extract induced cell cycle arrest at the G1 phase and apoptosis via reduced MMP in WiDr cells. Additionally, M. rubra extract significantly repressed telomerase and induced CHOP expressions in WiDr cells. Our results demonstrate that targeting telomerase and endoplasmic reticulum stress represents a promising strategy in colon cancer therapy, and M. rubra may have considerable potential for development as a novel natural product-based anticancer agent.